Pendampingan Program Pengembangan Edu-Ekowisata Mangrove Desa Tanjung Tiram Kabupaten Konawe Selatan Sulawesi Tenggara - Jamili, Jamili; Usman, Ida; Kadidae, La Ode; Suriana, Suriana; Rudia, La Ode Adi Parman; Yanti, Nur Arfa (Jurnal Pengabdian UNDIKMA, 2023)
The service activity aims to provide an understanding to the youth organization regarding the potential of mangrove ecosystems to be developed as Edu-Ecotourism in Tanjung Tiram Village, North Moramo District, South Konawe Regency, Southeast Sulawesi. The method of implementing this service was carried out education, practice, and mentoring. A questionnaire and data analysis were carried out descriptively to evaluate the increase in understanding of youth organization. The results of this community service activity showed that the understanding of youth organizations in Tanjung Tiram village increased regarding the conservation of the mangrove ecosystem and its potential to be developed as an edu-ecotourism village and in practice-assistance activities, 11 types of mangrove ecosystem constituents were identified in Tanjung Tiram Village. With a good understanding of the community and the high diversity of mangroves, Tanjung Tiram Village could be developed into a mangrove Edu-Ecotourism Village.